2014
DOI: 10.1016/j.egypro.2014.11.349
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Organic Ligand Transport in Supercritical CO2 Fluids and Impacts to Silicate Reactivity

Abstract: The interactions between water-saturated supercritical carbon dioxide, organics, and minerals are relatively unknown despite being important to carbon sequestration and enhanced hydrocarbon recovery activities. The goals of this study include verification of organic transport through scCO 2 and exploration of whether organic ligands can impact carbonate formation. An in situ near-infrared spectroscopic technique was used to probe supercritical CO 2 (scCO 2 )-organic mixtures at 35 °C and 100 bar. Observation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
(90 reference statements)
1
10
0
Order By: Relevance
“…Two of the low-temperature (<150 °C) studies , shown in Figure A examined carbonation when olivine was exposed to H 2 O-saturated scCO 2 (wet scCO 2 ), a non-aqueous reactive phase . Dissolution and carbonate precipitation in wet scCO 2 are facilitated by the formation of angstrom- to nanometer-scale water films on hydrophilic mineral surfaces. ,,, Work in this area, including studies of olivine carbonation, ,,,,,,,, has revealed unique reaction mechanisms and pathways for mineral carbonation that cannot be attained in aqueous media. For instance, the properties of Si-rich surface precipitates on carbonating silicates in wet scCO 2 are distinct from those that develop in aqueous experiments, and their development is remarkably sensitive to pressure–temperature conditions of the CO 2 . , Also, critical water film thicknesses are required for continuous coupled dissolution and precipitation. ,, Lastly, nucleation and growth of magnesite at low temperatures (≲65 °C) is promoted in wet scCO 2 , ,, likely due to the reduced level of hydration of Mg 2+ in nanoscale interfacial water films. , …”
Section: Knowledge Gaps and Research Frontiersmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the low-temperature (<150 °C) studies , shown in Figure A examined carbonation when olivine was exposed to H 2 O-saturated scCO 2 (wet scCO 2 ), a non-aqueous reactive phase . Dissolution and carbonate precipitation in wet scCO 2 are facilitated by the formation of angstrom- to nanometer-scale water films on hydrophilic mineral surfaces. ,,, Work in this area, including studies of olivine carbonation, ,,,,,,,, has revealed unique reaction mechanisms and pathways for mineral carbonation that cannot be attained in aqueous media. For instance, the properties of Si-rich surface precipitates on carbonating silicates in wet scCO 2 are distinct from those that develop in aqueous experiments, and their development is remarkably sensitive to pressure–temperature conditions of the CO 2 . , Also, critical water film thicknesses are required for continuous coupled dissolution and precipitation. ,, Lastly, nucleation and growth of magnesite at low temperatures (≲65 °C) is promoted in wet scCO 2 , ,, likely due to the reduced level of hydration of Mg 2+ in nanoscale interfacial water films. , …”
Section: Knowledge Gaps and Research Frontiersmentioning
confidence: 99%
“…At higher temperatures, including those relevant to CO 2 -enhanced geothermal systems, substantially more H 2 O can dissolve into the CO 2 -rich fluid, although the exact consequences for reactivity are unclear. For instance, at 250 °C and 500 bar along a prototypical geothermal-pressure gradient, the equilibrium concentration of water increases to ∼35 mol % (Figure B); such a dramatic increase would likely lead to enhanced solvation of both inorganic , and organic dissolved species. The increased water activity and clustering , at elevated temperatures will also likely induce ion formation, which has not yet been detected in wet scCO 2 .…”
Section: Knowledge Gaps and Research Frontiersmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we investigate CO 2 –H 2 O O-exchange in adsorbed H 2 O films on synthetic forsterite (Mg 2 SiO 4 ). In contrast to silica, the Mg 2+ content gives forsterite a particularly high potential to form various magnesium carbonate minerals in CO 2 –H 2 O fluids, such as those relevant to geologic carbon storage. The goals of this study are twofold: first, we establish the dominant process by which O-exchange occurs in thin H 2 O films on forsterite and determine whether H 2 O structure is the key controlling parameter, as is the case for silica. Second, we determine if there is a relationship between O-exchange rates and the reactivity of forsterite toward carbonation in variably humidified supercritical CO 2 (scCO 2 ), conditions that have direct relevance to CO 2 fluids in deep geologic reservoirs. , Specifically, previous studies have shown that a threshold H 2 O film thickness is necessary for rapid and continuous transformation of forsterite to magnesium carbonates in wet scCO 2 , although the exact origins of this reactivity threshold have remained unclear.…”
Section: Introductionmentioning
confidence: 99%